Detecção de Colisão Broad Phase com RAY KD-Tree: Uma Abordagem Eficiente e Adaptativa - Serpa, Ygor; Rodrigues, Maria Andréia (Proceedings of the SBC Undergraduate Research Contest (CTIC-SBC), 2015)
Several fast algorithms for Broad Phase collision detection have been proposed, but few of them have diverse applicability being, in most cases, limited to a small class of scenarios and/or of difficult configuration. In this work, we describe RAY KD-Tree, a new solution based on the use of kdimensional trees for an efficient, generic, and easily configurable execution, which is able to adapt automatically to the test scenarios and to the dynamics of their objects.